Diseño de un prototipo de laboratorio para el balanceo de líneas de producción a implementarse en la Universidad Técnica de Cotopaxi. - Rojas Arcentales, Víctor Arturo (2019)
This project to be presented as the design of a prototype of production lines that is included directly with processes of selection, packaging and classification, its purpose is the academic approach for the training process of the industrial engineers that demand the current companies, using elements of use that allow the student to develop competencies and useful skills for your professional performance that currently national or international companies require in a professional. The prototype is presented as a proposal to be implemented in the Technical University of Cotopaxi, the same that can be used by the faculty of Industrial Engineering and its purpose is the acquisition of indispensable technology for the learning of students of the Career, with this prototype has an aim of imparting a deep knowledge within the process automation directed towards the students with the purpose of creating a model of practices, in this way the students and teachers can detail an information precise and concise towards the work that will be done in this laboratory, in this way its results will be real and proven with high feasibility. The result is that the students of Industrial Engineering obtain an automated knowledge for their knowledge on the basis of process control, in the same way in their practices of related chairs as engineering in methods. The result is directed to the students of industrial engineering, who obtain an automated knowledge in processes including for their development a guide of laboratory practices in the same that specify the procedures and parameters to use in the appropriate practices.